Letter from James Scott, 13 August 1845, Ebenezer Chapel, West Coast - Scott, James, 1797-1869
Special meeting of the Demerara District Committee. Mr & Mrs Henderson to leave for England for health reasons; Mr Henderson to return as soon as possible.